Measure of Thermoelectric Power of CdSe Thin Films that Prepared with Different Depositions Rate. - Raad Saedon Sabri (مجلة جامعة الانبار للعلوم الصرفة, 2009)
In this paper CdSe thin films have been prepared deposited on galas substrate by thermal evaporation technique at thickness 250 nm with different depositions rate ( 0.2,0.4,0.6,0.8,1,1.2) nm/s and substrate temperatures ( Ts) (300,373,423,473)K . Thermoelectric power were measured to this films ,Seebak coefficient and activation energy were evaluated, the results shows that all films were of n-type conductivity and activation energy increases with dispositions rate and substrate temperature films prepared at 0.8 nm/s with 425 K and 1.2 nm/s with Ts (425 ,475 ) K , except that they were of p-type conductivity .